Rekonsiliasi antara Islam dan Local Wisdom dalam Kontekstualisasi Ḥadīth tentang Larangan Tashabbuh - Sulaemang L; Nur Hadi; Abdul Muiz Amir (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
This article focuses on the study of the contextualization of the meaning of the ḥadīth about tashabbuh using both macro and micro socio-historical study approach. The study was conducted to find the significance of the meaning contained in the ḥadīth about the prohibition of tashabbuh, using the study of ḥadīth literature and historical sources. The results of the study found that; (1) the study of the ḥadīth about the prohibition of tashabbuh cannot be understood by only using a textual-literal approach, because it can only narrow down the meaning of ḥadīth, so it is more likely to lead to a fundamentalist-radicalist understanding; (2) Studying the ḥadīths is to find the meaning behind the text, context, and contextualization of the ḥadīth, theologically normative aims to maintain the faith dan the belief in tawḥīd, while socially cultural aims to realize the Islamic foundation as tolerance and raḥmah; (3) there are two types of tashabbuh in the theological-normative domain; showing absolute prohibition, and social welfare; showing skill as long as it does not conflict with the basic rules of sharī'ah and realizes maṣlaḥah for human life.